Cover (OpenFOAM® Journal, 2021)
The first issue image is a collage of the first ever visualized simulation results of Prof. Hrvoje Jasak of an eddy detachment from over twenty years ago, with an eddy detachment of Chandan Bose from 2021. This symbolizes the incredible journey FOAM/OpenFOAM have made over the last years and decades. Hrvoje Jasak Wikki Ltd., Unit 459, Southbank House, Black Prince Road, London, SE1 7SJ, United Kingdom h.jasak@wikki.co.uk Chandan Bose Department of Applied Mechanics, Indian Institute of Technology Madras, Chennai 600036, India cb.ju.1991@gmail.com, http://www.chandanbose.com References Bose, C., Gupta, S., & Sarkar, S. (2021). Dynamic interlinking between near-and far-field wakes behind a pitching–heaving airfoil. Journal of Fluid Mechanics, 911.